A needle in (many) haystacks: Using the false alarm rate to sift gravitational waves from noise. Issue 1 (3rd February 2021) - Zheng, Yanyan; Cavaglià, Marco; Quitzow‐James, Ryan; Mogushi, Kentaro
Abstract : Yanyan Zheng, Marco Cavaglià, Ryan Quitzow‐James and Kentaro Mogushi explain how statistics helps scientists spot ripples in the fabric of space and time Abstract : Yanyan Zheng, Marco Cavaglià, Ryan Quitzow‐James, and Kentaro Mogushi explain how statistics helps scientists spot ripples in the fabric of space and time.